Foreign direct investment in Saudi Arabia’s post-pandemic ERA: Determinants and impact - Aldhawyan, Sulaiman (Edelweiss Applied Science and Technology, 2025)
This study investigates the key determinants of foreign direct investment (FDI) in Saudi Arabia during the post-pandemic era, focusing on the country’s ongoing economic diversification efforts under Vision 2030. The research aims to understand how macroeconomic indicators such as GDP growth, inflation, exchange rate stability, trade openness, and government expenditure affect FDI inflows. A mixed-methods approach was employed, combining descriptive analysis with multiple regression techniques using data from 2017 to 2023. The findings reveal that market size, trade openness, and income level are the most influential factors in attracting FDI, while inflation and unemployment exhibit a more nuanced impact. The results also highlight a significant rebound in FDI after 2020, driven by structural reforms and increased investor confidence. The study concludes that a stable and transparent investment climate is essential for sustaining FDI growth. The findings offer valuable insights for policymakers to enhance Saudi Arabia’s investment appeal by fostering regulatory stability, improving infrastructure, and supporting human capital development. These implications are particularly relevant as the Kingdom seeks to position itself as a competitive global investment hub in the evolving post-COVID global economy.